Genetic deletion of monoacylglycerol lipase leads to impaired cannabinoid receptor CB1R signaling and anxiety‐like behavior. (11th September 2015) - Imperatore, Roberta; Morello, Giovanna; Luongo, Livio; Taschler, Ulrike; Romano, Rosaria; De Gregorio, Danilo; Belardo, Carmela; Maione, Sabatino; Di Marzo, Vincenzo; Cristino, Luigia
Abstract: Endocannabinoids (eCB) are key regulators of excitatory/inhibitory neurotransmission at cannabinoid‐1‐receptor (CB1 R)‐expressing axon terminals. The most abundant eCB in the brain, that is 2‐arachidonoylglycerol (2‐AG), is hydrolyzed by the enzyme monoacylglycerol lipase (MAGL), whose chronic inhibition in the brain was reported to cause CB1 R desensitization. We employed the MAGL knock‐out mouse (MAGL−/−), a genetic model of congenital and sustained elevation of 2‐AG levels in the brain, to provide morphological and biochemical evidence for β‐arrestin2‐mediated CB1 R desensitization in brain regions involved in the control of emotional states, that is, the prefrontal cortex (PFC), amygdala, hippocampus and cerebellar cortex. We found a widespread CB1 R/β‐arrestin2 co‐expression in the mPFC, amygdala and hippocampus accompanied by impairment of extracellular signal‐regulated kinase signaling and elevation of vesicular glutamate transporter (VGluT1) at CB1 R‐positive excitatory terminals in the mPFC, or vesicular GABA transporter (VGAT) at CB1 R‐positive inhibitory terminals in the amygdala and hippocampus. The impairment of CB1 R signaling in MAGL−/− mice was also accompanied by enhanced excitatory drive in the basolateral amygdala (BLA)‐mPFC circuit, with subsequent elevation of glutamate release to the mPFC and anxiety‐like and obsessive‐compulsive behaviors, as assessed by the light/dark box and marble burying tests, respectively. Collectively, these data provide evidence for a β‐arrestin2‐mediated desensitization of CB1 R in MAGL−/− mice, with impact on the synaptic plasticity of brain circuits involved in emotional functions. In this study, the authors provide evidence that congenitally enhanced endocannabinoid levels in the neuronal circuits underlying anxiety‐like behavioral states (mainly medial prefrontal cortex, amygdala and hippocampus) lead to CB1R desenistization and anxiety and depression. MAGL−/− mice, a model of congenital overactivity of the eCB system, exhibited a compensatory impairment of CB1R signaling in anxiety‐associated brain areas and a subsequent change in excitatory/inhibitory tone associated with altered score in the marble burying and light/dark box test, in concomitance with anxiety and depression behavior states. These findings may have potential relevance to the understanding of the neurochemical effects of chronic CB1R overstimulation in cannabis abusers. Abstract : In this study, the authors provide evidence that congenitally enhanced endocannabinoid levels in the neuronal circuits underlying anxiety‐like behavioral states (mainly medial prefrontal cortex, amygdala and hippocampus) lead to CB1R desenistization and anxiety and depression. MAGL−/− mice, a model of congenital overactivity of the eCB system, exhibited a compensatory impairment of CB1R signaling in anxiety‐associated brain areas and a subsequent change in excitatory/inhibitory tone associated with altered score in the marble burying and light/dark box test, in concomitance with anxiety and depression behavior states. These findings may have potential relevance to the understanding of the neurochemical effects of chronic CB1R overstimulation in cannabis abusers.